Establishment and evaluation of qPCR and real‐time recombinase‐aided amplification assays for detection of largemouth bass ranavirus. Issue 7 (27th April 2022) - Guo, Yanmin; Wang, Yahui; Fan, Zhaobin; Zhao, Xianlin; Bergmann, Sven M.; Dong, Hanxu; Jin, Yuqi; Sun, Dongli; Mai, Qianyi; Liu, Weiqiang; Zeng, Weiwei
Abstract: Largemouth bass ranavirus disease (LMBVD) caused by largemouth bass ranavirus (LMBV) has resulted in severe economic losses in the largemouth bass ( Micropterus salmoide s) farming industry in China. Early and accurate diagnosis is the key measure for the prevention and control of LMBVD. In this study, a quantitative polymerase chain reaction (qPCR) and a real‐time recombinase‐aided amplification (real‐time RAA) assay were established for the detection of LMBV. The sensitivity and specificity of these two methods, and the efficacy for detection of LMBV from clinical samples were also evaluated. Results showed that the real‐time RAA reaction was completed in <30 min at 39℃ with a detection limit of 58.3 copies, while qPCR reaction required 60 min with a detection limit of 5.8 copies. Both methods were specific for LMBV, where no cross‐reactions observed with the other tested fish pathogens. Comparing the amplification results of both assays to the results obtained by virus isolation using 53 clinical tissue samples, results showed that the clinical sensitivity of real‐time RAA and qPCR were 93.75% and 100% respectively, and the clinical specificity of both were 100%. Our results showed that qPCR is more suitable for quantitative analysis and accurate detection of LMBV in the laboratory, while real‐time RAA is more suitable as a point‐of‐care diagnostic tool for on‐site detection and screening of LMBV under farm conditions and in poorly equipped laboratories.